Unravelling the dynamics of successful collaboration and the potential for community-based learning in child and youth care - Bhagwan, Raisuyah (Social Work/Maatskaplike Werk, 2025)
The aim of the research was to investigate successful collaborative community-university partnerships. The intention was to identify factors that contribute to effective service in rural spaces as transformative teaching and learning environments for final-year child and youth care students from a University of Technology in KwaZulu-Natal. Utilising a qualitative research methodology, the research design involved non-probability purposive sampling, with twelve students recruited for semi-structured interviews. Data analysis was conducted using thematic analysis to identify key themes related to the effectiveness of the engagement process and its impact on both students and the community. The findings highlight the importance of mutual trust, clear communication and shared goals in fostering successful collaborations. The study underscores the potential for community engagement projects not only to serve local needs, but also to enrich students' educational experiences, ultimately suggesting that thoughtful partnerships can lead to sustainable community engagement and enhanced learning outcomes.